Киевская Александрия: Владимир Маккавейский и Осип Мандельштам - Zel’chenko, Vsevolod; Ustinov, Andrei (Wiener Slawistischer Almanach, 2023)
The essay follows the history of a relationship between Vladimir Makkaveiskii and Osip Mandelshtam, two Modernist poets who met in Kyiv in 1919. It was there when Makkaveiskii suggested the two final lines for Mandelshtam’s poem “Na kamennykh otrogakh Pierii...”, also known as “The Turtle”, the story that is much discussed among his biographers. The authors reconstruct the context of Mandelshtam’s interactions with Makkaveiskii, including a thorough discussion of the latter’s poem “The Twilight of Alexandria”, that he wrote in the second half of April of 1919, and dedicated to Mandelshtam. The essay reёstablishes Makkaveiskii as a major poet in the war-torn Kyiv, and the influence he exercised in the city’s literary circles. It is accompanied by a selection of Makkaveiskii’s poems from his archives at Stanford University, most of which are published here for the first time.